Metro Manila motorists' commercial guide. (Philippine Motorists Guide, 1991)
This 14th volume guide contains useful driving tips and information about cars and car owners in general. A section called "Motorists' Buyers Guide" provides listings of business establishments solely in the automotive and allied industries within Metro Manila. The recreational and entertainment section, also called the 'pink pages' provides listings of entertainment places such as bowling, clubs, golf courses, etc. within Metro Manila.